Effect of the Substitution of S for Se on the Optical Absorption Spectra of the Glassy Alloys Ag1,6Ga1,6Ge31,2S61,6-xSex - Halyan, V.V.; Shevchuk, M.V.; Ivashchenko, I.A.; Kevshyn, A.H. (Physics and Chemistry of Solid State, 2016)
Optical absorption spectra of the glassy alloys Ag1,6Ga1,6Ge31,2S61,6-xSex in the range of 400-1000 nm at 80 and 300 K have been investigated. It was revealed that with increasing of Se the width of the energy gap of the glasses decreases. In samples with x = 13.1, 19.7, 26.2, 32.8, 45.9, 52.5 at 80 K the photoluminescence was observed. It has the vague of peak and half-width emission band ΔE≈0,26-0,30 eV, which is characteristic for the recombination luminescence of the disordered systems. Peculiarities of the optical absorption spectra and photoluminescence are in good correlation with Mott's and Davis' model for localization energy states in the disordered systems.